DAMPAK FENOMENA JUDI ONLINE TERHADAP DISORGANISASI SOSIAL PADA MAHASISWA DI BANDUNG - Ageng saepudin kanda S; Desi nurhalimah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. Gambling is a phenomenon that cannot be denied in society. Actually, the phenomenon of gambling is not something new in the lives of Indonesian people, because the habit of gambling has been around for a long time. The principle of the game is generally the same, namely the aim is to make a profit if you win the bet. The more money or items you bet, the more money you win. So the problem with this research is that many students are still tempted by lures like that which have a bad impact on the students themselves. This research method is qualitative where the data collected is descriptive in nature to provide an overview of what happens in the field. The results of this research were that there were 43 students out of 50 students who filled out the questionnaire who knew about online gambling, and of these 43 students, there were 22 people who were involved in online gambling games. This states that many students are involved in playing online gambling after learning about the game. students who are involved in playing online gambling. The consequences of being involved in online gambling for students include mental health disorders, financial losses, involvement in criminal acts, damage to social relationships, potential for addiction, and the risk of being involved in substance abuse. Keywords: Online Gambling, Students, Life, Impact